2020
DOI: 10.1186/s41043-020-00215-w
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative assessment of barriers and facilitators to implementing recommended infant nutrition practices in Mumbai, India

Abstract: Background Childhood malnutrition has been a longstanding crisis in Mumbai, India. Despite national IYCF (Infant Young Child Feeding) guidelines to promote best practices for infant/toddler feeding, nearly one-third of children under age five are stunted or underweight. To improve child nutrition, interventions should address the cultural, social, and environmental influences on infant feeding practices. This study is an in-depth qualitative assessment of family barriers and facilitators to implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 34 publications
1
28
0
3
Order By: Relevance
“…While some mothers struggled to balance the housework and programme participation, some fathers, those not in pairs, failed to even recognise that housework was a burden and even served as an obstacle for mothers' participation in the programme. Women in low‐income countries, although living in extended families, not only found it challenging to receive physical and emotional support from their families but also faced the pressure of living up to other family members' expectations (i.e., mothers‐in‐law) (Athavale et al, 2020; Jones et al, 2012). This pattern tends to aggravate when family members lack an understanding of the programme's main purpose.…”
Section: Discussionmentioning
confidence: 99%
“…While some mothers struggled to balance the housework and programme participation, some fathers, those not in pairs, failed to even recognise that housework was a burden and even served as an obstacle for mothers' participation in the programme. Women in low‐income countries, although living in extended families, not only found it challenging to receive physical and emotional support from their families but also faced the pressure of living up to other family members' expectations (i.e., mothers‐in‐law) (Athavale et al, 2020; Jones et al, 2012). This pattern tends to aggravate when family members lack an understanding of the programme's main purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Competence is crucial for CHWs to advise mothers consistently and correctly. Additionally, competence is required to reassure mothers of the correctness of promoted practices while increasing their confidence to implement these practices (Athavale et al, 2020; Burns et al, 2016). Furthermore, improving competence is crucial, as incorrect beliefs among CHWs have been associated with negative practices involving newborn babies (Smittenaar et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, mothers who are adequately informed and encouraged can defy adverse traditions and follow recommendations (Burns et al, 2016). By contrast, receiving conflicting information on IYCF may cause uncertainty among mothers about their own abilities, leaving them unable to translate information into practice (Athavale et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pattern suggests that some migrant families may have a better ability to implement recommended infant feeding practices compared to the overall population. One study conducted in informal settlements in Mumbai comprising of mainly migrants found that social support and self-efficacy for decision making are important factors determining mothers’ feeding behaviors [ 29 ]; it is possible that for some women, these constructs can improve during migration, as they are removed from traditional, sometimes oppressive, family structures. Additionally, migration can influence children’s diets (positively or negatively) through increased household income as well as exposure to new health and nutrition practices [ 30 ].…”
Section: Discussionmentioning
confidence: 99%